The Role of Silver Nanoparticles in a Treatment Approach for Multidrug-Resistant Salmonella Species Isolates - Farouk MM (Dove Medical Press, 2020)
Manar M Farouk,1 Amal El-Molla,1 Fayez A Salib,1 Yousef A Soliman,2 Mohamed Shaalan3 1Department of Internal Medicine and Infectious Diseases, Faculty of Veterinary Medicine, Cairo University, Giza 12211, Egypt; 2Central Laboratory for Evaluation of Veterinary Biologics (CLEVB), Cairo, Egypt; 3Department of Pathology, Faculty of Veterinary Medicine, Cairo University, Giza 12211, EgyptCorrespondence: Manar M FaroukDepartment of Internal Medicine and Infectious Diseases, Faculty of Veterinary Medicine, Cairo University, Giza 12211, EgyptTel +02 01067903499Email manarmagdy@cu.edu.egPurpose: The main objective of this study is to investigate the antibacterial activity of silver nanoparticles (AgNPs) against multidrug-resistant Salmonella isolates recovered from diarrheic  sheep and goatsMethods: This study used chemical reduction synthesis of AgNPs to evaluate their antimicrobial effects by estimation of minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) for each isolate using the microplate dilution method and tetrazolium salt reduction test to detect the viability percentage. In vivo treatment efficacy was assessed in mice by determining the viable count of Salmonella Enteritidis recovered from feces and by hematologic, biochemical and histopathologic examinations to confirm that use of AgNPs has no toxic or pathologic effects and to evaluate its ability in tissue regeneration following treatment.Results: All recovered strains were identified as MDR with a prevalence of 4% and 3.6% in sheep and goats, respectively. The results of TEM, DLS, Zeta potential, and FTIR revealed typical characteristics of the synthesized AgNPs. Silver nanoparticles showed antibacterial activity against all recovered strains with MIC of ≤ 0.02– 0.313 μg/mL (mean average 0.085± 0.126 μg/mL) and MBC of 0.078– 1.250 μg/mL (average 0.508± 0.315 μg/mL). In vivo efficacy of AgNPs was observed by a reduction in the number of viable S. Enteritidis recovered from feces in an S. Enteritidis infected mouse model, with complete shedding stopping between treatment days 4 and 6. Hematologic, serum biochemical, and histopathologic analyses proved the ability of AgNPs to suppress inflammatory reaction caused by S. Enteritidis infection.Conclusion: The study proved the effective ability of AgNPs to fight MDR Salmonella spp. in vitro and in vivo without adverse effects.Keywords: multidrug resistance, silver nanoparticles, Salmonella, mice, minimum inhibitory concentration, minimum bactericidal concentration